Comparing family property disputes in English and Singapore law: "Context" is everything - YIP, Man (Institutional Knowledge at Singapore Management University, 2021)
This paper examines why Singapore law has not followed English law in the area of beneficial ownership of family property. It points out that the landmark cases in the two jurisdictions are underpinned by different family paradigms.The English landmark cases are based on the unmarried cohabitants paradigm and the legal rules that have emerged from these cases are aimed at, whether successfully or not, ensuring a fair division of the family home upon the breakdown of these relationships. In contrast, the Singapore seminal judgments are underlaid by contests between children over their parents’ property which raised questions as to the parties’ true intentions and the legal techniques to determine that. In the main, this paper argues that the legal rules that emerge in a society are shaped by the conditions of that society: these rules are purpose-built to resolve the specific types of disputes that come through the judicial system, which are in turn moulded by the distinctive conditions of that society. The discussion also shows that whilst the courts in the two jurisdictions differ in the legal techniques which they apply to determine these disputes, they do not appear to differ greatly in their understanding of human interactions and complex family relationships.